A promising strategy for efficient electromagnetic interference shielding by designing a porous double-percolated structure in MWCNT/polymer-based composites. (November 2020) - Chen, Jia; Liao, Xia; Li, Shaojie; Wang, Wei; Guo, Fumin; Li, Guangxian
Abstract: Porous conductive polymer composites (CPCs) are supposed to be the most prospective substitutes for metal-based materials in the field of electromagnetic interference (EMI) shielding but are still confronted with the challenge of poor performance. To solve the dilemma, we firstly design a porous double-percolated structure in co-continuous polystyrene (PS)/polymethyl methacrylate (PMMA)/ MWCNT system with a judicious combination of melt blending and supercritical carbon dioxide (scCO2 ) foaming. At thickness of 2 mm and MWCNT content of 1.61 vol%, the porous composite possessed low-density (0.4 g/cm 3 ), high electrical conductivity (1.64 S/m) and efficient EMI shielding performance (23.08 dB). Moreover, the percolation threshold decreased from 0.18 to 0.14 vol%, and the specific EMI SE increased from 37.79 to 57.7 dB·cm 3 /g compared to the solid counterparts. This work offers a novel idea for the design of lightweight EMI shielding materials with high performance, exerting tremendous potential in electronics and aerospace fields.